Obese neuronal PPARγ KO mice are leptin sensitive but show impaired glucose tolerance and fertility - Fernandez, Marina Olga (2017)
PPARγ is expressed in the hypothalamus in areas involved in energy homeostasis and glucose metabolism. In this study, we created a deletion of PPARγ (BKO) in mature neurons in female mice to investigate its involvement in metabolism and reproduction. We observed that there was no difference in age at puberty onset between female BKOs and littermate controls, but the BKOs gave smaller litters when mated and fewer oocytes when ovulated. The female BKO mice had regular cycles but showed an increase in the number of cycles with prolonged estrus. The mice also had increased LH levels during the LH surge and histological examination showed hemorrhagic corpora lutea. The mice were challenged with a 60% high fat diet. Metabolically the female BKO mice showed normal body weight, glucose and insulin tolerance, and leptin levels but were protected from obesity-induced leptin resistance. The neuronal knockout also prevented the reduction in estrous cycles due to the HFD. Examination of ovarian histology showed a decrease in the number of primary and secondary follicles in both genotypes due to the HFD, but the BKO ovaries showed an increase in the number of hemorrhagic follicles. In summary, our results show that neuronal PPARγ is required for optimal female fertility, but is also involved in the adverse effects of diet-induced obesity by creating leptin resistance potentially through induction of the repressor Socs3.